Description of Coeliccia bhriulieci sp. nov. (Odonata: Zygoptera: Platycnemididae) from central Vietnam - To, van Quang; Phan, Quoc Toan; Tran, van Bang (Zootaxa, 2017)
Coeliccia bhriulieci sp. nov. (holotype male from Tay Giang district, Quang Nam province, central Vietnam, deposited in the Zoological collection of the Southern Institute of Ecology, Vietnam Academy of Science and Technology, Ho Chi Minh City, Vietnam) is described based on male specimens. The new species is easily distinguished from other Coeliccia species in the Southeast Asian region by the combination of its blue abdominal tip, black anal appendages and structure of genital ligula with two long flagella extending from lateral corners of apical segment.